Écologisation des pratiques agricoles et ancrages familiaux au territoire. Une comparaison de l’utilisation des produits phytosanitaires entre Camargue et Beaujolais - Carole Barthélémy; Aurélien Allouche; Gilles Armani; Gaïa Bonnet; Christelle Gramaglia; Laurence Nicolas (Développement Durable et Territoires)
The reduction in the use of pesticides is relevant to analyse the interactions between the ecologization of agricultural practices and their relationships with territories. Sociological surveys conducted in Camargue and Beaujolais allow to compare these interactions through two criteria of analysis. The first is the agricultural history of these two territories and their different relationships with environmental issues. The second element proposes to specifically question farming families as a social space which, by drawing a sort of territorial legitimacy, can make changes in the use of pesticides.